Profil Kemampuan Siswa dalam Menyelesaikan Soal Pilihan Ganda Kompetisi Sain Madrasah (KSM) di MAN 2 Kota Semarang - Fauzan Fauzan; Fenny Roshayanti; Nur Khoiri (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Abstact This study aims to describe the profile of students' ability to solve physics olympiad questions at MA Negeri 2 Kota Semarang. The research subjects with this qualitative approach were 30 students representing 6 classes of the science program from the physics olympiad competition. The results of this study found 3 profiles of abilities possessed by students participating in physics olympiad in answering questions, namely students were said to have high, medium and low abilities